Wood Quality of Ten-Year-Old Sentang (Azadirachta Excelsa) Grown from Seedlings and Rooted Cuttings - Abdullah Siam, Nordahlia (2009)
Seeds of sentang were exhibit recalcitrant and cannot be stored for a long period of time. So efforts have been made to propagate this species vegetatively via rooted cuttings technique. It is envisaged that for the technique to be deemed successful, the quality of wood that it produces should be comparable with or better than the wood extracted from the natural forest or established plantation via seedlings. The main objective of this study was to determine and compare the wood qualities of the trees grown from seedlings and rooted cuttings and to study the property variations within the tree. The specific objectives of these studies were to evaluate the macroscopic features, anatomical, physical, mechanical properties and resistance to fungal decay of sentang which grown from these two propagation techniques. Correlations between anatomical, physical and mechanical properties of the wood were also analysed. The studies of both types of wood were done at three different height levels, i.e bottom, middle and top and also in the sapwood and heartwood portion. Data were subjected to Analysis of Variance (ANOVA) and further analysed using Least Significant Difference (LSD) at p ≤ 0.05. The barks of both types of wood were smooth and pinkish grey. There was significant difference in colour of sapwood and heartwood between these two propagation techniques where the sapwood from seedling trees was lighter than those from rooted-cutting trees. However, the heartwood of the latter was darker. The mean percentage of sapwood-heartwood ratio was not significantly different between these two types of wood and the amount of sapwood-heartwood ratio increased towards the top. The anatomical structure in both types of wood is similar with typical sentang. Vessels are diffuse, solitary or multiple, round to oval shaped and filled with dark-coloured dried extractives deposits in the heartwood. Apotracheal and paratracheal parenchyma are present in both types of wood. Tangential section shows multiseriate rays which mostly 2-3 cells wide and heterocellular rays were observed in the radial section in both types of wood. The rooted-cutting wood showed higher value in fibre dimensions, vessel diameter and proportion of vessels, whereas vessel density and proportion of fibre were higher in the seedling wood and proportion of rays was not significantly different between both types of wood. Both the seedling and rooted-cutting wood showed a decreasing trend towards the top in fibre dimensions, vessel diameter and proportion of rays. Increasing trend was observed in vessel density and proportions of vessels and fibres. The sapwood exhibited higher value in fibre dimensions, proportion of rays and larger vessel diameter but lower value in vessel density and proportions of vessels and fibres than the heartwood in the seedling wood However, in the rooted-cutting wood there was no significant difference between sapwood and heartwood in proportion of rays, vessels and fibres. Both types of wood were not significantly different in basic density. Moisture content at green condition and shrinkages in green to air-dry and green to oven-dry conditions were higher in the rooted-cutting wood, but tangential and radial shrinkages from green to oven-dry conditions showed no significant difference between both types of wood. The physical properties of both types of wood showed a decreasing trend from the bottom to the middle of the tree and then a slight increasing trend towards the top. Basic density was higher in the sapwood but moisture content and shrinkages in both conditions were higher in the heartwood. Compression and shear parallel to the grain were higher in the seedling wood, however MOE was higher in the rooted-cutting wood and MOR showed no significant difference between the seedling and rooted-cutting wood. Mechanical properties showed increasing trend towards the top and higher values in the heartwood in both types of wood. All the mechanical properties in the seedling and rooted-cutting wood were significantly related with vessel diameter, proportion of fibres and volumetric shrinkage with small correlation. Basic density was weakly correlated with mechanical properties in this present study. Both types of wood were classified as resistant with rooted-cutting wood being more resistance to white rot fungus (Lentinus sajor-caju) than the seedling wood. The resistance of the wood to fungal decay decreased towards the top and higher resistance was shown in the heartwood than the sapwood portion.